Manufacturing confusion : BPL lists in Uttar Pradesh - Aman and Agrawal, Ashutosh (2014)
Multiplicity of ration cardholder lists has been found to be a cause for exclusion of the needy from access to subsidised food. A report from Allahabad district of Uttar Pradesh. - Reproduced.
Keywords: Poverty - India - Uttar Pradesh; Public distribution system - India - Uttar Pradesh; Public distribution system